AIN PRINCIPLES OF USING BUKHARA CITY’S ARCHITECTURAL MONUMENTS FOR MODERN PURPOSES - Tojiyev I.; Hojiyeva Sitorabonu Alijon qizi (Bright Mind Publishing, 2025)
The rich architectural heritage of Bukhara city and its utilization for modern purposes while preserving its historical and cultural significance, enhancing it, and passing it on to future generations without damage is considered a critical issue. Bukhara, a city renowned for its grand historical monuments, requires these monuments to be adapted for new purposes in line with contemporary demands and needs. This article encompasses all these aspects, emphasizing the enhancement of the functional significance of historical monuments through the use of modern architectural and urban planning technologies.
Keywords: Bukhara, architectural monuments, historical heritage, urban planning, innovations, cultural preservation, civilization, science, legacy.